Designing self-reflective visualizations in patient-cantered systems - Visvalingam A.; Dhillon J.S.; Gunasekaran S.S.; Hoe A.C.K. (Science Publishing Corporation Inc, 2023)
Self-care applications are mostly featured with visuals that educate users to comprehend their health status in taking a proactive role in their healthcare. It is crucial to ensure that these visuals are adequate and meets the expectations of the users. In this study, healthcare visualisation design factors were reviewed from existing studies in identifying their relevance to self-care visuals. The study also conducted a focus group study (FGD) with a group of mobile application users to understand their perception and expectations towards healthcare visuals presented in self-care applications. Results indicate that existing guidelines for healthcare visuals are focused on a specific type of application and they mostly emphasise the usability aspects of the visual and neglect its functionality. The identified themes from the FGD are motivation & commitment, customizability, personalisation, accessibility, complex yet comprehensible graphs, alerts & proactive support, and trust & privacy. Users are expecting healthcare visuals that are self-reflecting, comprehensive and user-friendly in enabling them to better understand their health conditions. A combination of design factors is necessary to aid the development of self-care visuals in health support applications. Hence, the study proposed a conceptual model that lists a set of design principles for self-reflective visualisations in novel health support applications. 2018 Authors.